Ab interno trabeculectomy: patient selection and perspectives - Vinod K (Dove Medical Press, 2016)
Kateki Vinod, Steven J Gedde Bascom Palmer Eye Institute, University of Miami Miller School of Medicine, Miami, FL, USA Abstract: Ab interno trabeculectomy is one among several recently introduced minimally invasive glaucoma surgeries that avoid a conjunctival incision and full-thickness sclerostomy involved in traditional glaucoma surgery. Ablation of the trabecular meshwork and inner wall of Schlemm’s canal is performed in an arcuate fashion via a clear corneal incision, alone or in combination with phacoemulsification cataract surgery. Intraocular pressure reduction following ab interno trabeculectomy is limited by resistance in distal outflow pathways and generally stabilizes in the mid-to-high teens. Relief of medication burden has been demonstrated by some studies. A very low rate of complications, most commonly transient hyphema and intraocular pressure elevations in the immediate postoperative period, have been reported. However, available data are derived from small retrospective and prospective case series. Randomized, controlled trials are needed to better elucidate the potential merits of ab interno trabeculectomy in the combined setting versus phacoemulsification cataract surgery alone and to compare it with other minimally invasive glaucoma surgeries. Keywords: ab interno trabeculectomy, glaucoma, intraocular pressure, minimally invasive glaucoma surgery, surgical outcomes